2014
DOI: 10.1080/17461391.2014.944874
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of second lactate turnpoint using two different criteria in competitive cyclists

Abstract: The aim of this study was to determine the relative and absolute reliability of second lactate turnpoint using fixed and individual blood lactate method in competitive cyclists. Twenty-eight male, well-trained cyclists (30.2 ± 10.1 years, 72.0 ± 7.4 kg, 177.3 ± 4.7 cm) were recruited to participate in this study. Cyclists completed two incremental cycling tests to exhaustion over a period of 7 days to determine their peak power output, maximal oxygen uptake, maximal heart rate, maximal blood lactate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The time course of [La] vs. work rates was graphically interpolated and LT 2 was determined using the IAT methodology, i. e. 1.5 mmol.L − 1 above the point of minimum ratio between [La] and work rate [12]. The agreement between IAT and MLSS as well as IAT reliability has been described elsewhere [10,17]. HR, VO 2 and RPE at IAT were also identified by linear interpolation between two segments.…”
Section: Graded Exercise Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course of [La] vs. work rates was graphically interpolated and LT 2 was determined using the IAT methodology, i. e. 1.5 mmol.L − 1 above the point of minimum ratio between [La] and work rate [12]. The agreement between IAT and MLSS as well as IAT reliability has been described elsewhere [10,17]. HR, VO 2 and RPE at IAT were also identified by linear interpolation between two segments.…”
Section: Graded Exercise Testmentioning
confidence: 99%
“…Specifically, no study has compared FTP against the individual anaerobic threshold (IAT). We have previously shown that IAT agrees more with MLSS than other LT methods [10] and presents high intraindividual reliability [17], suggesting this method could be a more robust measure to test the validity of FTP. Alternatively, a time to exhaustion (TTE) at FTP 20 could provide further evidence for the validity of the concept, but, to our knowledge, this evidence has not been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum and the lactate threshold were assessed, using the same test, on the SRM cycle ergometer (SRM Italia, Lucca, Italy) with the same settings (height and fore-aft position of the seat, height and distance of the handlebar, and length of the pedal crankarms) and the same type of bicycle pedals for each subject. The original incremental protocol to exhaustion to determine maximum calls for a minimum of five and a maximum of nine 4-minute stages, each with resistance increments between a minimum of 20 and a maximum of 50 watts [ 26 ] and has been found to be highly reliable for the lactate threshold assessment in cyclists [ 27 ]. Although the protocol called for an intensity of 40% of maximum for the first stage, we decided to use 30% in light of the fact that to determine the lactate threshold, the blood concentration of lactate at the end of the first stage should not be significantly higher than the resting value [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The test was interrupted when the cyclist was unable to maintain the cadence for more than 5 seconds or stopped voluntarily. Previous study 25 have suggested a variation of the 2.6% in ICT performance, using fixed methods. Besides is a test well-established and often used in research 3,11,26 , the psychophysiological variables evaluated by ICT are highly correlated with cycling performance 26 .…”
Section: Incremental Cycling Test (Ict)mentioning
confidence: 99%